A Comparative Study of Health Care Seeking Behavior of Women of Reproductive Age for Sexually Transmitted Diseases / Reproductive Tract Infections in The Rural and Urban Areas of Bareilly District - Singh, Arun; Mahmood, Syed Esam; Pandey, Sachin; Pandey, Amiya (National Journal of Community Medicine, 2012)
Objectives: The study was conducted with an objective to study the treatment seeking behaviour of women of reproductive age group (15-45 years) in both rural and urban areas of the District along with estimation of the cases of STDs/RTIs as per WHO’s syndrome case definitions Methodology: A cross sectional study was conducted during May-June 2010 among women of reproductive age group (15-45 years) in the urban and rural areas of Bareilly District to study their Health Care Seeking behavior for Sexually Transmitted Diseases (STDs)/Reproductive Tract Infections (RTIs). The two stage cluster sampling technique was adopted. A structured questionnaire was used to interview the study participants by house to house surveys. Each woman from selected household was interviewed in private about her reproductive history, clinical history (as per WHO's syndrome case definition) and place from where the treatment of STDs/RTIs was taken. Statistical analysis was done with SPSS computer software. Chi (x2) square test used, p value was calculated, p value less than 0.05 was considered for the statistical significance. Results: Out of total 620 women studied (310 each from urban and rural areas), 25.81% of rural and 6.77% of urban respondents had suffered from RTIs/STDs. Among these abnormal vaginal discharge (9.43%) was the commonest problem encountered in rural areas whereas lower abdominal pain (5.53%) was commonest in the urban areas. Government health facilities (District hospitals/CHCs/PHCs/SCs) were the main sources from where the treatment was sought by the women from both areas i.e. Urban (52.38) and Rural Areas (51.25%).